Survey Tingkat Kerjasama Siswa Ekstrakurikuler Bola Basket Di Sman 2 Klari - Novanto Cristover; Bambang Ismaya; Abdul Salam (Jurnal Ilmiah Wahana Pendidikan, 2022)
Basketball extracurricular is an extracurricular that is found outside and inside the school. This extracurricular is a sports extracurricular that usually exists in various schools, one of which is in SMA Negeri 2 Klari which is seen from the participation and participation of students in a positive direction. The students were very enthusiastic about participating in the training activities carried out by the trainer. but it is not easy to give the school in non-technical matters does not create a solid and strong level of student cooperation. The lack of cooperation in this team is easy to disagree and depend on each other. The existence of several indicators that have been carried out indicates that it is not solid on the basketball extracurricular survey at SMA Negeri 2 Klari. This research approach uses an approach when viewed from the type of data presented. the cooperation of extracurricular ball students at SMA Negeri 2 Klari for the academic year 2021/2022 obtained the lowest score (minimum) 126, the highest score (maximum) 155, the average (mean) 143, the median value (median) 144, the value that occurs frequently (Mode) ) 147 Standard Deviation (SD) 8 Based on the results of the analysis or survey data and discussion, it can be concluded that the level of cooperation of basketball extracurricular students at SMA Negeri 2 Klari for the 2021/2022 academic year is in the "Very Low" category of 10% (3 participants students), “Low” by 20% (6 students), “Medium” by 30% (9 students), “High”by 30% (9 students), and "Very High" by 10% (3 students). Keywords: Survey, Cooperation Level, Extracurricular, and Basketball.